Pengaruh Latihan Resistance Band terhadap Kecepatan Shooting dalam Olahraga Hockey - Fikry Saadillah Fadil; Asep Angga Permadi; Irwan Hermawan (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to determine the effect of resistance band training on shooting speed in hockey. The method used was an experiment with a quantitative approach employing a one-group pretest-posttest design. The study sample was selected using total probability sampling and consisted of 15 participants from the hockey extracurricular program at SMAN 11 Garut. The instrument used was a shooting speed test with the aid of measuring devices such as a speed gun or the Pitchlab app. Data were analyzed using descriptive statistics, a normality test, and a paired-sample t-test at a significance level of 0.05. The results showed an increase in the mean score from the pretest to the posttest. The normality test indicated that the data were normally distributed (Sig. > 0.05). The results of the paired-sample t-test showed a significance value of 0.000 (< 0.05), indicating a significant effect. Thus, it can be concluded that resistance band training is effective in improving shooting speed in hockey. This study has limitations regarding the relatively small sample size and the absence of a control group, so the results cannot yet be widely generalized. Therefore, future research is recommended to use a larger sample, include a control group, and examine other variables such as shooting accuracy and power to obtain more comprehensive results.